Coagulantes orgânicos e sulfato de alumínio aplicados no tratamento de efluente de indústria cervejeira - Janz, Fellipe Jhordã Ladeia (2018)
The beer production process generates a large amount of effluent, consuming up to 10L of water for each liter of beer, and the vast majority becomes effluent, containing a large quantity of organic matter, which can cause environmental problems if not treated. Knowing the pollutant potential of the brewery effluent, a comparison was made between three different coagulants (extracted from Moringa oleifera, Tannin and Aluminum Sulphate) for different effluent conditions, which was obtained from three different points in the treatment of effluent, where point A - the effluent after the preliminary treatment, point B - the effluent after treatment by anaerobic lagoons and the point C - the final effluent. The experiment was performed in Jar-Test using a concentration of 9 mL.L-1 of coagulant, and the whole procedure was done in triplicate with collections at the times of 3, 13, 23 and 33 minutes of sedimentation. The parameters of apparent color, turbidity, electrical conductivity, pH, temperature, chemical oxygen demand and total solids were analyzed. The best results of apparent color reduction and turbidity were obtained using the effluent collected at point A, and all coagulants had percentages above 84% of apparent color reduction and greater than 89% for turbidity reduction, being the largest reduction of apparent color obtained with Moringa oleifera and the highest turbidity reduction using Aluminum Sulphate. The electrical conductivity was influenced when the coagulant extracted from the Moringa oleifera seed was used due to the saline solution present. The removal of total solids had the best results at point A, the highlight was the Tannin with 35% of removal, while the Aluminum Sulphate obtained advantage in points B and C. The chemical oxygen demand obtained its best result when applied the treatment with Tannin coagulant in the effluent collected at point A. So after the accomplishment of the present study it is recommended the application of the coagulant Tanino at point A, because at this point of collection the organic coagulant presented high values of removal of apparent color and turbidity, and managed to obtain greater removal of chemical oxygen demand when compared to other coagulants.